2006
DOI: 10.1371/journal.ppat.0020116
|View full text |Cite
|
Sign up to set email alerts
|

EC5S Ubiquitin Complex Is Recruited by KSHV Latent Antigen LANA for Degradation of the VHL and p53 Tumor Suppressors

Abstract: Cellular protein degradation pathways can be utilized by viruses to establish an environment that favors their propagation. Here we report that the Kaposi's sarcoma–associated herpesvirus (KSHV)-encoded latency-associated nuclear antigen (LANA) directly functions as a component of the EC5S ubiquitin complex targeting the tumor suppressors von Hippel-Lindau (VHL) and p53 for degradation. We have characterized a suppressor of cytokine signaling box-like motif within LANA composed of an Elongin B and C box and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
207
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(212 citation statements)
references
References 64 publications
5
207
0
Order By: Relevance
“…The existence of multiple, mutually inclusive complexes can explain why targeted approaches such as coimmunoprecipitation and overexpression-based transcriptional experiments that are conducted in cells lacking the KSHV episome consistently find evidence for p53:LANA interactions (7,10,23,83,97,100), whereas phenotypic analyses of PEL or less sensitive, mass spectrometry (MS)-MS-based screens (4, 84) of PEL could not find evidence for a prominent p53:LANA complex. Further support for multiple independent complexes comes from our half-life analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of multiple, mutually inclusive complexes can explain why targeted approaches such as coimmunoprecipitation and overexpression-based transcriptional experiments that are conducted in cells lacking the KSHV episome consistently find evidence for p53:LANA interactions (7,10,23,83,97,100), whereas phenotypic analyses of PEL or less sensitive, mass spectrometry (MS)-MS-based screens (4, 84) of PEL could not find evidence for a prominent p53:LANA complex. Further support for multiple independent complexes comes from our half-life analysis.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-induced HIF 1α stabilization, as VHL loss, could cooperate in organizing host defenses and have cellular consequences that in some cases can inhibit viral replication (49,50). However, in other instances of persistent viral infection, HIF-1 activation can lead to the activation of the proangiogenic program and oncogenic transformation as a consequence (11,(51)(52)(53)(54). Therefore, considering the primary role of HIF 1α in immune defense, it is not surprising that cells have evolved auxillary mechanisms to rapidly sustain the stabilization of HIF 1α, for instance through the degradation of VHL protein.…”
Section: E G F P P E G F P -S O C S 1 B O X P E G F P -S O C S 3 B O mentioning
confidence: 99%
“…Several viruses encode for their own substrate receptors possessing the BC-box motif and are thus able to interact with EloB/ C cellular adaptor, thereby modifying the cellular ubiquitin E3 ligase complex and their target proteins selection (10)(11)(12)(13)(14)(15)(16)(17). We have demonstrated that the CELO (Chicken Embryo Lethal Orphan) Adenovirus early protein Gam1 is one of such BC boxcontaining proteins that is able to associate with both Cullin2 and Cullin5 to reconstitute active E3 ligase complexes and target the SUMO E1 enzyme (SAE1/SAE2 heterodimer) for degradation (18,19).…”
mentioning
confidence: 99%
“…Two previous reports have suggested that upon exogenous expression, LANA interferes with p53 and inhibits its transcriptional activity (26,27). More recently, LANA was also suggested to function as a component of the EC5S ubiquitin complex targeting p53 for degradation (28). However, these findings have not progressed toward a mechanistic explanation of how the virus overcomes normal cellular barriers or provided opportunities for therapy.…”
Section: Introductionmentioning
confidence: 99%